La frontera en la memoria cinematográfica española: mitos, utopías y quimeras - García Ballesteros, Enrique (Historia y Comunicación Social, 2007)
This article defines and analyses two models of frontier. There two concepts assimilate to the two meanings of frontier in English. The first one is related to the territorial advancement of a given people and imply social, political, economic and cultural interchanges. The second one is the spatial frontier, in which the psychological effects of facing the unknown constitute its leading feature. From this point of view, ‘frontier cinema’ is defined here as a unique filmic genre. This article examines the Spanish production of this particular genre and the way in which myths, utopias, chimeras accounting to political interests and ideological influences in different historical contexts have shaped it’s the plot.